Fifth Asia-Pacific Conference on ... And Fourth Optoelectronics and Communications Conference on Communications, 1999
DOI: 10.1109/apcc.1999.820500
|View full text |Cite
|
Sign up to set email alerts
|

GaInAsP/InP quantum-wire lasers

Abstract: Abstract-Present status of GaInAsP/InP long-wavelength quantum wire lasers, fabricated by a method using electron beam exposure, dry etching, and two-step organometallic vapor-phase epitaxy, is described from aspects of low-damage interface formation and size uniformity of quantum wire structures. Even though superior lasing properties attributed to sharper gain spectrum over that of quantum well structure have not been realized yet, polarization anisotropic feature of the quantum wire structure and formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Figure 1.7 shows the calculated gain spectra of different quantized dimensions in the case of lattice-matched GaInAs/InP under the same injection carrier density [11]. Not only the sharpness of the gain spectrum but also its symmetric shape of lower dimensional structures was found to be very promising for narrow spectral chirp under a high-speed direct modulation and a narrow-linewidth operation due to reduced linewidth enhancement factor [11,12]. Therefore, the threshold current, differential quantum efficiency, and linewidth of Q-wire and Q-box lasers have been expected to be superior to those of Q-film lasers [13].…”
Section: Gain Medium Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1.7 shows the calculated gain spectra of different quantized dimensions in the case of lattice-matched GaInAs/InP under the same injection carrier density [11]. Not only the sharpness of the gain spectrum but also its symmetric shape of lower dimensional structures was found to be very promising for narrow spectral chirp under a high-speed direct modulation and a narrow-linewidth operation due to reduced linewidth enhancement factor [11,12]. Therefore, the threshold current, differential quantum efficiency, and linewidth of Q-wire and Q-box lasers have been expected to be superior to those of Q-film lasers [13].…”
Section: Gain Medium Structuresmentioning
confidence: 99%
“…Since the epitaxial layers containing the active region are typically much thinner than the substrate, it is obviously advantageous to mount the laser in the epi-down configuration to minimize the thermal resistance [15][16][17][18]. The gain spectra of different quantized dimensions in the case of lattice-matched GaInAs/InP under the same injection carrier density [11] The epi-down structure is shown in Fig. 1.9, and it replaced the epi-up structure and has been applied in the packaging of high power semiconductor lasers [17].…”
Section: Physical Structurementioning
confidence: 99%
“…It is a direct indicator in determining the quality of semiconductor materials that are fabricated device [10]. The equation of threshold current density ( ) can be rewritten as [11]: (1) where q is the electronic charge, d is the thickness of one active layer, Nw is the number of active layers, is the in-plane space filling factor of the active regions (ρ=W/Λ), and Nth is the threshold carrier density. For QW (2)…”
Section: Theoretical Partmentioning
confidence: 99%
“…The semiconductor quantum wires, one of the low-dimensional structures that possess many special properties, have drawn the attention of scientists [18][19][20][21][22]. These structures could be applied to create high-speed lasers [23,24], quantum electron waveguides [25], resonant tunneling field-effect transistors [26,27], or telecommunication networks [28]. Recently, studies of movement and interaction among electrons in the quantum wires have shown the quantum effects that can lead to various applications in the new quantum technology [29].…”
Section: Introductionmentioning
confidence: 99%